2002
DOI: 10.1159/000065006
|View full text |Cite
|
Sign up to set email alerts
|

Role of GABA<sub>B</sub> Receptor in the Regulation of Excitatory Synaptic Transmission in Trigeminal Motoneurons

Abstract: The aim of the present study was to determine if excitatory synaptic transmission onto trigeminal motoneurons is subject to a presynaptic modulation by γ-aminobutyric acid (GABA) via GABAB receptor in this system. Whole cell recordings were made from trigeminal motoneurons in longitudinal brain stem slices taken from 8-day-old rats. Monosynaptic excitatory postsynaptic potential (EPSP) activity was evoked by placing bipolar stainless steel electrodes dorsal-caudal to the trigeminal motor nucleus. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The jaw-closing muscles are far stronger than the jaw-opening muscles [15]. Min et al [23] investigated trigeminal motoneurons and found that baclofen decreases the mean frequency but not the mean amplitude of mEPSP, which is accompanied by a reduction in 1/CV 2 and an increase in the failure rate. They suggest that excitatory synaptic transmission to motoneurons is subjected to presynaptic modulation by GABA B receptors.…”
Section: Organ Culture Model To Study Muscarinic Receptors G Proteinmentioning
confidence: 99%
“…The jaw-closing muscles are far stronger than the jaw-opening muscles [15]. Min et al [23] investigated trigeminal motoneurons and found that baclofen decreases the mean frequency but not the mean amplitude of mEPSP, which is accompanied by a reduction in 1/CV 2 and an increase in the failure rate. They suggest that excitatory synaptic transmission to motoneurons is subjected to presynaptic modulation by GABA B receptors.…”
Section: Organ Culture Model To Study Muscarinic Receptors G Proteinmentioning
confidence: 99%